FREEDOM OF EXPRESSION VS. RIGHT TO PRIVACY: THE ROLE OF ECHR IN MODELLING CIVIL LIABILITY FOR DAMAGE - Zdraveva, Neda (Правен факултет „Јустинијан Први“ - Скопје, 2021)
The European Convention on Human Rights in Article 8 provides that everyone has the right to respect for their private and family life. This is generally known as the right to privacy, in which the public authority may not interferebut also should create mechanisms for its protection. Article 10 of the ECHR provides that everyone has the right to freedom of expression. The exercise of the freedom, since it carries with duties and responsibilities, may be subject to restrictions, necessary in a democratic society, in the interest of intel alia protection of therights of others including their privacy. How these two rightsinterrelate and what is to be done in case of ‘conflict’ are one of the key questions when it comes to liability for damage that arises from the breach of the right to privacy. This is of particular interest when it comes to the work of the mediawhen providing insight into the private life of persons. The key question is when such exposure is to be considered relevant for the public interest. On a national level, the right to privacy is guaranteed by the Constitution. So is the freedom of expression. The breach of the right to privacy may lead to liability for damage if all conditions for the arise of such obligation are met. The paper examines and discusses when the breach of the privacy will (not) give rise to a right to claim damages for the breach of the right of privacy having in mind the need to balance this right and the freedom of expression.
Keywords: privacy, reputation, freedom of expression, ECHR, liability, damage